Influence of profitability on firm value: Data from transportation sector - Supitriyani Supitriyani; Astuti Astuti; Khairul Azwar (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
This study aimed to analyze and test the effect of stock returns, activity, profitability, and liquidity on firm value. We are using a sample of 14 companies obtained through the purposive sampling method on the transportation sub-sector companies listed on the Indonesia Stock Exchange. The results of this study indicate that stock returns, activity, profitability, and liquidity have a significant effect on firm value simultaneously. Partially, stock returns and profitability have a significant positive impact; activity has no significant positive impact, and liquidity has a significant negative effect on firm value.